Integrating environmental DNA and trawl surveys to assess seasonal dynamics of fish communities in the Oujiang River Estuary - Chen Weifeng; Ruan Huiting; Wang Wei; Xu Kaiping; Peng Xin; Zhu Rong; Lu Yumiao; Ye Shen; Lin Hungdu; Wang Chen; Zhou Xiaofeng (Frontiers in Marine Science, 2026)
Introduction Monitoring of estuarine fish biodiversity is often constrained by the inherent limitations of traditional survey methods and the complex, dynamic environmental conditions of estuarine habitats. Environmental DNA (eDNA) metabarcoding has emerged as a robust molecular tool for aquatic biodiversity assessment. Nevertheless, its complementary potential to conventional bottom trawling remains understudied in estuarine ecosystems. In this study, we integrated eDNA metabarcoding and bottom trawling to investigate the spatiotemporal dynamics of fish diversity in the Oujiang River Estuary (ORE). Methods Fish assemblage data were collected seasonally across four sampling periods at five fixed sites within the ORE. MiFish-U primers targeting the 12S rRNA gene were utilized for eDNA amplification. And twelve aquatic environmental variables were quantified to disentangle correlations between fish community structure and ambient environmental conditions. Multiple statistical approaches, including alpha diversity analysis, Principal Coordinate Analysis (PCoA) and PERMANOVA, were applied to quantify spatiotemporal shifts in fish assemblages, identify fish-environment correlations, and compare community discrepancies between the two survey methods. Results and discussion The combined approach detected a total of 100 fish species across 84 genera and 45 families. Specifically, eDNA metabarcoding identified 72 fish species, while bottom trawling captured 48 species, with only 20 species shared between the two methods. Fish assemblages exhibited distinct seasonal variations, with both survey methods revealing higher species richness during wet seasons. Temporal fluctuations in water temperature, dissolved oxygen, salinity and nutrient concentrations constituted the primary environmental drivers structuring estuarine fish assemblages, whereas spatial heterogeneity across sampling sites exerted no statistically significant influence on community composition. eDNA metabarcoding showed unique advantages in detecting pelagic, migratory, cryptic and endangered fish species, supporting effective biodiversity monitoring in topographically intricate estuarine waters. In contrast, bottom trawling provided reliable morphological identification and quantitative abundance data for demersal fish taxa, which helped resolve ambiguous species annotations derived from eDNA sequencing. In addition, seven IUCN-listed threatened fish species were documented during the field investigation. Collectively, our findings demonstrate that eDNA metabarcoding and bottom trawling serve as highly complementary, rather than mutually exclusive, tools for fish biodiversity assessment. The integration of the two methods enables a more comprehensive and accurate evaluation of estuarine fish diversity. This study validates the feasibility and efficacy of the combined monitoring framework for macrotidal estuaries and provides valuable scientific references for the ecological conservation and management of the Oujiang River Estuary as well as other similar coastal ecosystems.

Assessing the population genetic structure of yellow croaker in China: Insights into the ecological and genetic consequences of artificial breeding on natural populations - Jigui Yuan; Xuan Zhuang; Lisheng Wu; Hungdu Lin; Yulong Li; Lina Wu; Jixiang Yao; Jinxian Liu; Shaoxiong Ding (Aquaculture, 2024)

Deep genome-wide divergences among species in White Cloud Mountain minnow Tanichthys albonubes (Cypriniformes: Tanichthyidae) complex: Conservation and species management implications - Chao Li; Han Xiao; Xiuxia Zhang; Hungdu Lin; Kathryn R. Elmer; Jun Zhao (Molecular Phylogenetics and Evolution, 2023)

Resource Status and Effect of Long-Term Stock Enhancement of Large Yellow Croaker in China - Jigui Yuan; Hungdu Lin; Lisheng Wu; Xuan Zhuang; Junkai Ma; Bin Kang; Shaoxiong Ding (Frontiers in Marine Science, 2021)
The large yellow croaker, Larimichthys crocea , was once the most abundant and economically important marine fish in China. Thus far, it has also been the most successful mariculture fish species in China. However, its wild stock severely declined in the 1970s because of overexploitation, and therefore hatchery release has been carried out for stock enhancement since 2000. As a migratory fish, large yellow croaker was divided into three geographical stocks according to ambiguous morphological and biological characteristics in early documents. To investigate the identity of wild large yellow croaker populations and assess the influence of hatchery supplementation on wild populations, a total of 2,785 cultured individuals and 591 wild individuals were collected from 91 hatcheries and six wild populations along the coast of mainland China and analyzed using two mitochondrial genes [cytochrome oxidase I ( COI ) and cytochrome b ( Cyt b )] and one nuclear gene ( RyR3 ). The higher haplotype diversity and moderate nucleotide diversity of wild large yellow croaker indicated that overexploitation, which caused a sharp decrease in biomass, did not lead to a loss of genetic diversity. According to phylogenetic construction and network analysis, the absence of a significant population structure pattern revealed a single panmictic population of wild large yellow croaker with exception of a population collected from the Sansha Bay, which showed high genetic relatedness to the cultured population, suggesting significant genetic effects resulting from stock enhancement. Overall, our study suggests no genetic differentiation in the entire wild population of large yellow croaker, which means that we have great flexibility in mixing and matching farmed and wild populations. However, since the result showed that domestication, the relaxation of purifying selection, increased genetic loads, and maladapted farmed fish will be at a selective disadvantage when cultured juveniles are released in the wild, the effectiveness of stock enhancement and the negative impact of hatchery-wild fish hybridization on the wild population must be carefully evaluated in future.